Major natural resource management concerns in South Asia - Gill, Gerard J. (International Food Policy Research Institute, 1995)
South Asia's food requirements are likely to grow at least 100 percent by the year 2020, while the region's natural resource base is likely to shrink. Gill advocates a transition from today's cereal-based, land -extensive, water-intensive production system to an agriculture more in keeping with the region's natural resource endowment. He cites increased investment in research and extension as a way out of the quandary of high population density and rising demand for food in South Asia.